Ankle injury prevention programs for soccer athletes are protective : A level-I meta-analysis - Grimm, N. L.; Jacobs, J. C.; Kim, J.; Amendola, A.; Shea, K. G. (The Journal of Bone & Joint Surgery (American Volume), 2016)
BACKGROUND: Soccer has one of the highest rates of ankle injury in sports for both males and females. Several injury prevention programs have been developed to address this concern. The purposes of this study were to conduct a meta-analysis of ankle injury prevention programs for soccer players, assess the heterogeneity among the studies, and evaluate the reported effectiveness of the prevention programs. METHODS: A systematic search of the literature was conducted in PubMed (MEDLINE), Embase, CINAHL (Cumulative Index to Nursing and Allied Health), and the Cochrane Central Register of Controlled Trials (CENTRAL) database. Studies were limited to clinical investigations of injury prevention programs specific to the ankle in soccer players. Title, abstract, and full-text review were utilized to identify articles that met the inclusion criteria. The Cochrane Q test and I(2) index were independently used to assess heterogeneity among the studies. Sensitivity analyses were performed to assess heterogeneity. The pooled risk difference was calculated by random-effects models with use of the DerSimonian-Laird method. Publication bias was assessed with a funnel plot and Egger weighted regression technique. RESULTS: Ten studies met the inclusion criteria as randomized controlled trials. A total of 4,121 female and male soccer athletes were analyzed for ankle injuries. Significant heterogeneity was found among studies of ankle injury prevention (p = 0.002), with an I(2) index of 65.2%. For studies of ankle injury prevention programs, the risk ratio was 0.60 (95% confidence interval, 0.40 to 0.92) and a significant reduction in the risk of ankle injury was found in the prevention group (p = 0.002). No evidence of publication bias was found among the included studies. CONCLUSIONS: This meta-analysis of studies regarding ankle injury prevention programs identified a significant reduction in the risk of ankle injury. Future high-quality research designs with a low risk of bias are necessary to further evaluate the effectiveness of specific exercises and the optimal timing and age at intervention for the prevention of ankle injuries in the athletic soccer player. LEVEL OF EVIDENCE: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.